Antimicrobial study of biosurfactants from Lactobacillus strains against skin pathogens - Vecino, Xanel (2016)
[Excerpt] Human skin microflora is composed by resident1 temporarily resident and transient microbial species. Therefore, gram-positive bacteria from the genera Propionibacterium, Staphylococcus, Micrococcus, Corynebaderium and Acinetobacter are the majority microorganisms present in the resident microflora [1 ]. For instance, Staphylococcus epidermidis is the main constituent of skin microflora, which protects the human skin from infections; whereas Staphylococcus aureus is a common transient species, which causes skin infections [2]. Anti-bacterial preservatives such as triclosan, methylparaben or bronopol, among others, are currently used as ingredients in the skin and oral care cosmetic products. However, there is a growing demand for cosmetics free of synthetic preservatives [3]. In this sense, biosurfactants from lactic acid bacteria, which are generally recognized as safe by the American Food and Drug Administration, are natural compounds that exhibit antimicrobial activity and therefore, could be used as an alternative to the chemically synthetized preservatives. The aim of this study was to evaluate the antimicrobial activity of biosurfactants obtained from two different Lactobacillus strains (L. pentosus and L. paracasef) against skin pathogenic microorganisms. [...]